Catheter ablation of atrial fibrillation in patients with left ventricular systolic dysfunction: a systematic review and meta-analysis - Anselmino, Matteo; Matta, Mario; D'Ascenzo, Fabrizio; Bunch, T Jared; Schilling, Richard J; Hunter, Ross J; Pappone, Carlo; Neumann, Thomas; Noelker, Georg; Fiala, Martin; Bertaglia, Emanuele; Frontera, Antonio; et al. (Circulation. Arrhythmia and electrophysiology, 2014)
BACKGROUND: Catheter ablation of atrial fibrillation (AFCA) is an established therapeutic option for rhythm control in symptomatic patients. Its efficacy and safety among patients with left ventricular systolic dysfunction is based on small populations, and data concerning long-term outcome are limited. We performed this meta-analysis to assess safety and long-term outcome of AFCA in patients with left ventricular systolic dysfunction, to evaluate predictors of recurrence and impact on left ventricular function. METHODS AND RESULTS: A systematic review was conducted in MEDLINE/PubMed and Cochrane Library. Randomized controlled trials, clinical trials, and observational studies including patients with left ventricular systolic dysfunction undergoing AFCA were included. Twenty-six studies were selected, including 1838 patients. Mean follow-up was 23 (95% confidence interval, 18-40) months. Overall complication rate was 4.2% (3.6%-4.8%). Efficacy in maintaining sinus rhythm at follow-up end was 60% (54%-67%). Meta-regression analysis revealed that time since first atrial fibrillation (P=0.030) and heart failure (P=0.045) diagnosis related to higher, whereas absence of known structural heart disease (P=0.003) to lower incidence of atrial fibrillation recurrences. Left ventricular ejection fraction improved significantly during follow-up by 13% (P<0.001), with a significant reduction of patients presenting an ejection fraction <35% (P<0.001). N-terminal pro-brain natriuretic peptide blood levels decreased by 620 pg/mL (P<0.001). CONCLUSIONS: AFCA efficacy in patients with impaired left ventricular systolic function improves when performed early in the natural history of atrial fibrillation and heart failure. AFCA provides long-term benefits on left ventricular function, significantly reducing the number of patients with severely impaired systolic function.
Keywords: tepový objem; atrial fibrillation; Ventricular Dysfunction, Left; obnova funkce; odds ratio; Stroke Volume; Humans; Natriuretic Peptide, Brain; catheter ablation; lidé středního věku; Recurrence; Middle Aged; rozdělení chí kvadrát; fibrilace síní; funkce levé komory srdeční; Time Factors; Peptide Fragments; heart failure; Risk Factors; mužské pohlaví; Chi-Square Distribution; Recovery of Function; natriuretický peptid typu B; katetrizační ablace; výsledek terapie; rizikové faktory; peptidové fragmenty; časové faktory; meta-analysis; recidiva; biologické markery; Treatment Outcome; ženské pohlaví; Catheter Ablation; lidé; Odds Ratio; dysfunkce levé srdeční komory; Atrial Fibrillation; Biomarkers; Ventricular Function, Left; Systole; Male; systola; Female